Development of website-based construct 2 interactive multimedia for elementary school students at natural science learning content - Handayani, Arzita; Sari, Elok Fariha (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Limitations in providing innovative learning media can affect learning activities, such as lack of desire to learn and low learning outcomes. Therefore, this research aims to develop website-based construct 2 interactive multimedia products as IPAS learning media on the material of various landscapes and livelihood professions of class IV elementary schools. This research is a type of Reseach and Development research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used are questionnaires and tests. Validation results from media experts 91.6% and material experts 90% get the category "very feasible" to use. Website-based construct 2 interactive multimedia gets a very good response from teachers and students. The results of the teacher's response were 90.9% and the results of the students' response were 90%. The results of the effectiveness test of website-based construct 2 interactive multimedia got an N-gain of 0,770 in the "High" category. Thus it is concluded that website-based construct 2 interactive multimedia can be said to be very feasible to use in learning activities and very effective for improving student learning outcomes, especially in IPAS learning material on the variety of landscapes and livelihood professions of class IV elementary school communities.